1997
DOI: 10.1074/jbc.272.3.1665
|View full text |Cite
|
Sign up to set email alerts
|

Intronic Enhancer Activity of the Eosinophil-derived Neurotoxin (RNS2) and Eosinophil Cationic Protein (RNS3) Genes Is Mediated by an NFAT-1 Consensus Binding Sequence

Abstract: The eosinophil-derived neurotoxin (EDN) and eosinophil cationic protein (ECP) are both small, cationic ribonuclease toxins that are stored in and secreted by activated human eosinophilic leukocytes. We have previously shown that optimal expression of the EDN gene is dependent on an interaction between an intronic enhancer element or elements and the 5 promoter region. Here we present evidence demonstrating that the gene encoding ECP is regulated in an analogous fashion and that an intronic enhancer element fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…In addition to the difference in transcript size, the intron of the mouse gene is substantially longer than that found in the human gene (984 vs. 351 nucleotides). It has been shown for human EDN/RNase 2 (Tiffany et al 1996), ECP/RNase 3 (Handen and Rosenberg 1997), and mouse Ear2 (Dyer et al 2004) that the noncoding exon and intron contain important regulatory elements and perhaps these are disrupted or rearranged in the mouse RNase 6 gene, resulting in a more restricted expression profile compared to the human orthologue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the difference in transcript size, the intron of the mouse gene is substantially longer than that found in the human gene (984 vs. 351 nucleotides). It has been shown for human EDN/RNase 2 (Tiffany et al 1996), ECP/RNase 3 (Handen and Rosenberg 1997), and mouse Ear2 (Dyer et al 2004) that the noncoding exon and intron contain important regulatory elements and perhaps these are disrupted or rearranged in the mouse RNase 6 gene, resulting in a more restricted expression profile compared to the human orthologue.…”
Section: Discussionmentioning
confidence: 99%
“…The promoter and the first intron contain multiple consensus transcription factorbinding sites. Recently, it was shown that the nuclear factor of activated T cells (NF-AT) site plays an important role in the activity of the intronic enhancer in undifferentiated HL-60 cells [14], whereas the intronic PU.1 site is involved in the regulation of the gene in the eosinophil-differentiated HL-60-eos cells [13]. Over the last few years several myeloid-specific genes and their regulatory sequences have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…A high degree of homology can be an indicator for a specific function of a sequence even if it is located in an intron. In recent years, an increasing number of intronic sequences has been identified exerting a stimulatory 8,9 or inhibitory 10,11 function in terms of gene regulation.…”
mentioning
confidence: 99%